Drug-induced encephalopathy in cervical cancers with ifosfamide - I Nyoman Gede Budiana; Melinda Febiani; Pande Kadek Aditya Prayudi (Neurologico Spinale Medico Chirurgico, 2020)
Ifosfamide, whether in single or combination regimen, have been used in many centers for end-stage cervical cancer cases or recurrent cases. Although it has shown satisfying results, especially in cases of platinum resistance, this drug is related to various side effects, such as encephalopathy. In this study, several cases of acute encephalopathy in cervical cancer patients treated with ifosfamide chemotherapy are described. This study is a retrospective study using all cervical cancer cases receiving ifosfamide chemotherapy in Sanglah Hospital Denpasar from 2015 to 2017. The diagnosis of encephalopathy was established by neurologists. Data obtained from hospital medical records. There were five patients who received the second line ifosfamide-cisplatin chemotherapy regimen at Sanglah Hospital Denpasar from 2015 to 2017. They had received first-line chemotherapy in form of 6 series of paclitaxel carboplatin and some of them received additional therapy in the form of external radiation and brachytherapy. Ifosfamide-cisplatin chemotherapy was given from one to six series, depending on the patient's response. Side effects in the form of encephalopathy appeared in four patients, while one patient managed to recover. Ifosfamide encephalopathy is a side effect that needs to be monitored. It has varied symptoms, but the symptoms are generally mild. Analysis of patient risk factors, patient education, and preparation for the management of encephalopathy should be performed in all cases that will receive ifosfamide. Methylene blue and thiamine can be used as a prophylactic and therapeutic choice for this condition.